CREATIVE INDIVIDUALITY IN JADIDISM POETRY: INTRODUCTION OF NEW IDEAS AND IMAGES - Rakhmonova Dildora (European Journal of Humanities and Educational Advancements, 2024)
This article analyzes the evolution of the poetic image in the work of Tolagan Khojamerov Tavallo, a representative of Jadid literature in Uzbekistan. The study examines the main trends in changes in the poet’s poetic style, analyzes innovations in the use of traditional literary images, such as a flower, a lover, an enemy, a nightingale, and identifies the rethought meanings of these symbols in the context of modern literary tradition. These images symbolize beauty, love, friendship, history and other important aspects of Uzbek society. Newspapers, youth, fathers, aristocrats and other images are also used to create characters and reflect sociocultural realities. Examples and illustrations are given to demonstrate the stages of development of poetic images and their transformation in Tavallo’s work, and questions of the influence of sociocultural factors on this artistic development are also raised.